Modified atmosphere packaging maintains the postharvest quality of baby mustard (Brassica juncea var. gemmifera) - Sun, Bo; Di, Hong-Mei; Lin, Pei-Xing; Wang, Gui-Yuan; Li, Zhi-Qing; Wang, Ya-Ting; Fang, Peng-Cheng; Cui, Ce-Xian; Zhang, Fen; Zheng, Yang-Xia (Emirates Journal of Food and Agriculture, 2022)
Baby mustard has increased in popularity among consumers. However, baby mustard is highly perishable. In this study, the influence of various modified atmosphere packaging (MAP) on the visual quality and content of soluble sugars and glucosinolates of baby mustard during postharvest storage was studied. Baby mustard was packed in no holes (M0), microholes (M1), or macroholes (M2) polyethylene bags respectively, and then stored at 20 °C. M1 and M2 inhibit the deterioration of visual quality of baby mustard, maintained the glucosinolates content, as well as prolonged the shelf life compared with non-wrapped plants, and M2 was the most effective in delaying the decline in visual parameters. By contrast, M0 accelerated the deterioration of postharvest quality. These findings indicate that M2 provides a promising approach for maintaining the visual and nutritional quality of postharvest baby mustard at ambient temperature.